High-resolution Geophysics in the Investigation of the Inner Structure of Walls and Columns of Batalha Abbey - Matias, M. J. Senos
Knowledge of walls and other structural elements construction characteristics and techniques is mandatory in the maintenance and restoration of historical buildings. Such information is obtained from documents or by comparing with monuments of the same period. Documents are difficult to obtain and comparison with other buildings can be inaccurate. The use of direct invasive techniques may be considered but they are likely to damage structures or compromise buildings stability. Thus, indirect high-resolution methods are adapted to these investigations. This work describes a GPR and a Seismic Transmission Tomography survey to investigate the walls and columns of the 14th century Batalha Abbey (UNESCO heritage site). High-resolution GRP data revealed the dimensions and thicknesses of different walls and the structure and nature of materials inside them. The Seismic Transmission Tomography survey, supported by high-resolution photogrammetry scanning for accurate positioning of sources and geophones, was carried out to investigate the Abbey columns. Seismic velocities distribution inside the columns characterized their interior and clarified the nature of the materials used. Columns construction followed the same technique and used the same materials. However, each column depicts a different velocity zonation that could correspond to different stages of deterioration for each one.